2020
DOI: 10.1101/2020.01.24.918201
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Adaptive divergence generates distinct plastic responses in two closely relatedSeneciospecies

Abstract: 16Phenotypic plasticity can maintain population fitness in novel or changing environments if it allows the 17 phenotype to track the new trait optimum. Understanding how adaptation to contrasting environments 18 determines plastic responses can identify how plasticity evolves, and its potential to be adaptive in response 19 to environmental change. We sampled 79 genotypes from populations of two closely related but ecologically 20 divergent ragwort species (Senecio, Asteraceae), and transplanted multiple cl… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
36
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2

Relationship

5
1

Authors

Journals

citations
Cited by 8 publications
(40 citation statements)
references
References 74 publications
(97 reference statements)
4
36
0
Order By: Relevance
“…Etna (2,000m and above) where it occurs on lava flows that are covered by snow each winter. A previous reciprocal transplant of cuttings of both species showed that the two species have evolved different forms of plasticity associated with adaptive divergence to habitats at these contrasting elevations (Walter et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Etna (2,000m and above) where it occurs on lava flows that are covered by snow each winter. A previous reciprocal transplant of cuttings of both species showed that the two species have evolved different forms of plasticity associated with adaptive divergence to habitats at these contrasting elevations (Walter et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…There is also support from phylogenetic studies for an increase in diversification with elevation (Merckx et al, 2015), particularly in high elevation 'island-like habitats' (Hughes & Eastwood, 2006). Moreover, phylogenetic evidence indicates that many high-elevation endemics across the globe are phylogenetically young taxa resulting from recent fast diversification (Winkworth et al, 2004;Merckx et al, 2015;Walter et al, 2020). This fact fits well with the geological evolution of Etna, which, although started almost 600,000 years ago on the sea floor, really a true stratovolcano (named ''Ellittico'') exceeding 3,000 m in altitude, is formed only from about 100,000 years ago (De Beni et al, 2011).…”
Section: Elevational Gradient Of Species Richness/endemismmentioning
confidence: 89%
“…). These leaf measurements represent leaf morphology and investment traits that show plastic responses to the abiotic environment in S. chrysanthemifolius (Walter et al 2020b), and in other plant systems, including sunflowers (Royer et al 2009). We also used a Dualex instrument (Force-A) to measure the chlorophyll, flavonol and anthocyanin pigment content of the leaf.…”
Section: (2) Fitness In the Novel Environment Correlates With Geneticmentioning
confidence: 99%
“…Etna (Table S1; also see Fig. 1 in Walter et al 2020b). Where possible, we sampled individuals that were at least ten meters apart from each other to minimize chances of sampling close relatives.…”
Section: Genotype Sampling and Crossing Designmentioning
confidence: 99%
See 1 more Smart Citation